Executive function and effortful control—Similar and different evidence from big data analysis - Chae, Soo Eun (Frontiers in Psychology, 2022)
The current study explored commonalities and similarities between executive function (EF) and effortful control (EC) based on a systematic analysis of the major empirical studies published between 2013 and 2022. A result of big data analysis using bibliographic information published in the World of Science (WoS) captured the following points: 1. EC is the efficiency of executive attention that incorporates inhibitory control (IC), attentional control, activation mainly related to temperament. On the other hand, EF is the efficiency of self-directed action that encompasses IC, working memory (WM), and shifting/ cognitive flexibility in particular focuses on the cognitive aspect. 2. EF research has overwhelmingly outnumbered EC research (2,000 EF studies vs. 50 EC studies per year). 3. According to a co-word analysis with keyword co-occurrences, the subject of preschool students and individual differences co-occurred in EF studies. 4. EC usually occurs with working memory and early childhood. In the more detailed analysis of the articles, the EF and EC studies used younger subject groups than older subject groups. EC studies were especially likely to use subjects in early childhood. 5. The Delis-Kaplan Tests of Executive Functioning System (D-KEFS) was the most commonly used test for EF. In contrast, the EC used self-report surveys such as the ATQ (Adolescent Temperament Questionnaire). This research illustrates and discusses key findings in the EC and EF data and provides suggestions for future study directions.